2018
DOI: 10.1103/physrevb.97.125303
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of cavity-enhanced single-photon emission from optical two-photon Raman processes

Abstract: We consider cavity-enhanced single-photon generation from stimulated two-photon Raman processes in three-level systems. We compare four fundamental system configurations, one Λ-, one Vand two ladder (Ξ-) configurations. These can be realized as subsystems of a single quantum dot or of quantum-dot molecules. For a new microscopic understanding of the Raman process, we analyze the Heisenberg equation of motion applying the cluster-expansion scheme. Within this formalism an exact and rigorous definition of a cavi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…For the single photon emission of interest in the present work we have previously shown that the Raman resonance condition non-trivially depends on the shape of the control pulse triggering the emission [15,20]. Moreover, the Raman process can also act as a source of excitation-induced quantum interference instead of as a source of single-photon emission [20]. Both these aspects play an increasingly important role for elevated control pulse intensities and generally tend to undermine our quest for entering the on-demand regime for single Raman photon generation.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…For the single photon emission of interest in the present work we have previously shown that the Raman resonance condition non-trivially depends on the shape of the control pulse triggering the emission [15,20]. Moreover, the Raman process can also act as a source of excitation-induced quantum interference instead of as a source of single-photon emission [20]. Both these aspects play an increasingly important role for elevated control pulse intensities and generally tend to undermine our quest for entering the on-demand regime for single Raman photon generation.…”
Section: Introductionmentioning
confidence: 75%
“…To unlock the full potential of quantum applications high single-photon emission probabilities are required, exceeding 66% for linear quantum computing [21] and 50% for Boson sampling [22]. For the single photon emission of interest in the present work we have previously shown that the Raman resonance condition non-trivially depends on the shape of the control pulse triggering the emission [15,20]. Moreover, the Raman process can also act as a source of excitation-induced quantum interference instead of as a source of single-photon emission [20].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations